IMPROVING STUDENTS’ SPEAKING PERFORMANCE THROUGH VLOG - Mandasari, Berlinda; Aminatun, Dyah (English Education:Journal of English Teaching and Research, 2020)
The shifting of English language learning from conventional way to technology-based learning is popular nowadays. It is necessary to identify the effect of using technology towards the students’ performance. One of technology that currently well-known is Vlog. This study aims at identifying the improvement of the students’ performance after learning English using Vlog. The participants of this study is 40 students majoring English Education Department of Universitas Teknokrat Indonesia. They enrolled in Transactional Conversation subject where practicing English through vlog was carried out. The design of this research is quantitative study in which the researcher employed pre-test and post-test. The result of pre-test and post-test was analyzed by using statistics descriptive and statistics inferential (Mann-Whitney U). The result of analysis is there is significant improvement towards students’ performance after learning English by using Vlog.